Management of advanced invasive thymomas: a review of literature - Bryl, Maciej; Ramlau, Rodryg; Dyszkiewicz, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2004)
Thymoma is a rare neoplasm deriving from epithelial tissue of thymus. Paraneoplastic syndromes are relatively common especially those which develop on autoimmune basis. For a number of years the classification of thymoma has been stated as non-homogenous, yet recently they have been stated as such and their clinical importance has been analyzed. This paper is a review of literature concerning histology, clinical issues and treatment of thymoma. Since thymoma is rare there are relative difficulties in carrying out prospective randomized trials. The paper presents literature concerning both the retrospective analysis of treated cases and conducted trials performed by a large international group of researchers. The paper focuses on chemotherapy due to new standards of systemic treatment of this neoplasm emerging as well as changes which are made to the management of thymoma due to chemotherapy. Results of chemotherapy in treating thymoma are positive and a significant overall response rate as well as median survival time and relapse free survival time can be achieved. Reports about such results are coming from not only retrospective observations but also prospective trials. More and more frequently chemotherapy is used not as a further stage of treatment but as part of basic treatment as induction chemotherapy before surgery or radiotherapy. ADOC, PAC, PE and VIP combinations are most frequently used. The best results were achieved using ADOC combination but possible advantage of this combination should be confirmed by a randomized phase III trial.